2013
DOI: 10.1589/jpts.25.605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Training with Breathing Resistance and Sustained Physical Exertion to Improve Endurance Capacity and Respiratory Muscle Function in Healthy Young Adults

Abstract: [Purpose] In this study, combined training with breathing resistance and sustained physical exertion was carried out to evaluate its physiological effects and its effect on improve endurance capacity. [Subjects and Methods] The subjects were nine healthy adults (mean age 20.4, SD ± 1.7 years). The combined training group (n = 5) carried out 6 weeks of combined training using a cycle ergometer, with exercise load tests and respiratory function tests performed before and after the training. The results of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
3
29
1
Order By: Relevance
“…When looking at VO 2 max and PPO, the control group increased VO 2 max by 13.5%, and PPO by 9.9% versus increases in VO 2 max of 16.5% and PPO by 13.6% in the mask group. Kido et al (2013) found similar results after 6 weeks of continuous exercise comparing resistive breathing during exercise to exercise alone. The resistive breathing group improved VO 2 max by 18.5% and PPO by 11.1% and the control exercise group improved by VO 2 max by 11.7% and PPO by 11.5%.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…When looking at VO 2 max and PPO, the control group increased VO 2 max by 13.5%, and PPO by 9.9% versus increases in VO 2 max of 16.5% and PPO by 13.6% in the mask group. Kido et al (2013) found similar results after 6 weeks of continuous exercise comparing resistive breathing during exercise to exercise alone. The resistive breathing group improved VO 2 max by 18.5% and PPO by 11.1% and the control exercise group improved by VO 2 max by 11.7% and PPO by 11.5%.…”
Section: Discussionmentioning
confidence: 53%
“…Kido et al (2013) conducted a 6-week training study comparing the physiologic responses of using breathing resistance during continuous exercise to continuous exercise alone; breathing resistance was provided by a ReBNA mask-like device with valves providing inspiratory and expiratory resistance. It was found that training between 75% and 85% of HRR improved VO 2 peak significantly in both exercise only (11.7%) and resistance breathing (18.5%) groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this hypothesis, a 6-week combined training with breathing resistance and sustained physical exertionwas performed using a mask-type device that created inspiratory and expiratory resistance while only allowing inhalation through the nose and exhalation through the mouth. A comparison between the results of the 6-week combined training with breathing resistance and sustained physical exertion and a similar intensity physical training without respiratory load showed significant improvement in maximal voluntary ventilation and VT [9]. Compared to the respiratory training methods noted above, combined training with breathing resistance and sustained physical exertion has the following distinctions.…”
Section: Introductionmentioning
confidence: 92%
“…A previous study aimed at proving the efficacy of combined training with breathing resistance and sustained physical exertion [9]; however the underlying mechanism of how this combined training improves the respiratory function has not been revealed.…”
Section: Introductionmentioning
confidence: 99%